2021
DOI: 10.1038/s41598-021-96479-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase-amplitude coupling between infraslow and high-frequency activities well discriminates between the preictal and interictal states

Abstract: Infraslow activity (ISA) and high-frequency activity (HFA) are key biomarkers for studying epileptic seizures. We aimed to elucidate the relationship between ISA and HFA around seizure onset. We enrolled seven patients with drug-resistant focal epilepsy who underwent intracranial electrode placement. We comparatively analyzed the ISA, HFA, and ISA-HFA phase-amplitude coupling (PAC) in the seizure onset zone (SOZ) or non-SOZ (nSOZ) in the interictal, preictal, and ictal states. We recorded 15 seizures. HFA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The regular paces (e.g. the less variable inter‐burst intervals, Figures 3 and 7) of network oscillations unlocked by concurrent inhibition of pre‐synaptic and post‐synaptic A‐channels are consistent with the stereotyped pathological oscillations found in epilepsy patients (Hashimoto et al, 2021; Liu et al, 2018; Matsumoto et al, 2013). More uniform paces of discharges presumably may lead to hypersynchronous network activities, which would be simpler coding and carry less information, compared with more variable normal oscillations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The regular paces (e.g. the less variable inter‐burst intervals, Figures 3 and 7) of network oscillations unlocked by concurrent inhibition of pre‐synaptic and post‐synaptic A‐channels are consistent with the stereotyped pathological oscillations found in epilepsy patients (Hashimoto et al, 2021; Liu et al, 2018; Matsumoto et al, 2013). More uniform paces of discharges presumably may lead to hypersynchronous network activities, which would be simpler coding and carry less information, compared with more variable normal oscillations.…”
Section: Discussionsupporting
confidence: 78%
“…Our present results demonstrate that the A-channels-tuned glutamatergic input serves as an extrinsic drive for rhythmic activity in the BLA network. Disinhibition of glutamatergic transmission by Achannel (K v 1.4 and K v 4.3) inhibition would switch the network activities from apparent random firings to synchronous pacemaking reverberations, with the same frequencies in the low delta-like range as those in a seizure network (Chou et al, 2020;Hashimoto et al, 2021).…”
Section: What Is the Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective study, we enrolled six patients with drug-resistant focal epilepsy who underwent intracranial electrode placement for presurgical invasive electroencephalography (EEG) and who were admitted to Osaka University Hospital between July 2018 and July 2019 (Table 1). Some patients (P1 to P5) in this study were the same patients as those included in our previous study (Hashimoto et al, 2021a(Hashimoto et al, , 2021b.…”
Section: Subjects and Study Settingmentioning
confidence: 99%
“…Studies related to pathological PAC have demonstrated that ictal HFA amplitude is coupled with δ (Nariai et al, 2011) or θ (Ibrahim et al, 2014) bands. Our previous studies investigating FBTCS have shown that PAC between infra-slow activities and HFAs precede ictal HFAs (Hashimoto et al, 2020b(Hashimoto et al, , 2021a. Moreover, previous studies have mainly focused on ictal PAC or PAC of the seizure onset zone (SOZ), and it remains unclear how PAC dynamically changes throughout FBTCS.…”
Section: Introductionmentioning
confidence: 99%